African American rhetoric(s) : interdisciplinary perspectives - Richardson, Elaine B., 1960-; Jackson, Ronald L., 1970- (Southern Illinois Univ Press, 2007)
African American Rhetoric(s): Interdisciplinary Perspectives is an introduction to fundamental concepts and a systematic integration of historical and contemporary lines of inquiry in the study of African American rhetorics. Edited by Elaine B. Richardson and Ronald L. Jackson II, the volume explores culturally and discursively developed forms of knowledge, communicative practices, and persuasive strategies rooted in freedom struggles by people of African ancestry in America. Outlining African American rhetorics found in literature, historical documen.